Angular distributions for the inelastic scattering of NO(X(2)Π) with O2(X(3)Σg(-)) - Brouard, M; Gordon, S; Nichols, B; Squires, E; Walpole, V; Aoiz, F; Stolte, S (AIP Publishing, 2017)
The inelastic scattering of NO(X2Π) by O2(X3Σg-) was studied at a mean collision energy of 550 cm(-1) using velocity-map ion imaging. The initial quantum state of the NO(X2Π, v = 0, j = 0.5, Ω=0.5, 𝜖 = -1, f) molecule was selected using a hexapole electric field, and specific Λ-doublet levels of scattered NO were probed using (1+1(')) resonantly enhanced multiphoton ionization. A modified "onion-peeling" algorithm was employed to extract angular scattering information from the series of "pancaked," nested Newton spheres arising as a consequence of the rotational excitation of the molecular oxygen collision partner. The extracted differential cross sections for NO(X) f→f and f→e Λ-doublet resolved, spin-orbit conserving transitions, partially resolved in the oxygen co-product rotational quantum state, are reported, along with O2 fragment pair-correlated rotational state population. The inelastic scattering of NO with O2 is shown to share many similarities with the scattering of NO(X) with the rare gases. However, subtle differences in the angular distributions between the two collision partners are observed.